PERANAN PENGUKURAN KINERJA KARYAWAN DALAM MENINGKATKAN QUALITY OF SERVICE BALAI BESAR PELAKSANAAN JALAN NASIONAL V - Maharani, Dhian Aji Putri (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2013)
The purpose of this research is to find out how the role of Quality of service and the implementation of performance measurement which is provided by BBPJN V to the customers. The type of research is qualitative research which is carried out by analyzing the primary data. The data analysis technique is carried out by applying Mini Research Question and Main Research Question. This research is carried out by performing written semi structured interview and face to face. It can be concluded from the results and analysis of the research that the quality of service and employee performance measurement artifacts are still facing problems such as shortage of technical personnel in the laboratory supervisor BBPJN V Sidoarjo, energy is the most important technical supervisor, then still a lack of awareness of consumer / customer to follow counseling, seminars, employee attitudes and behavior that still may be illegal. The existence of material testing equipment facilities kekurangnya so many consumers / customers that can not be handled in the laboratory BBPJN V Sidoarjo but should be referred to another laboratory. It can be seen from the efforts being made to make improvements, and supported with consumer complaints book so that it can determine indirectly consumer complaints. Overall quality of service provided is quite good. So with the improvements made to the Laboratory BBPJN V Sidoarjo mempu compete with similar instintusi.Keywords: Service Quality, Performance Measurement and Qualitative Research